Effect of different additives on the production of bacterial cellulose from pineapple waste - Muhammad Fuad Fikri, Amir (2013)
The pineapple peel wastes contain high concentration of biodegradable organic material such as carbohydrate that can be utilized for the production of organic acid.With the goal of being economically competitive and overcome the problem of disposal of the waste,pineapple waste can be potentially used to enhance the production of bacterial cellulose. Bacterial cellulose is known as polysaccharide and usually it been used traditionally in food industry and the latest it is used as a material for medical application.In this research,bacterial cellulose was produced by Acetobacter xylinum from pineapple waste as a fermentation medium with three different types of additives that is sodium alginate, microcrystalline cellulose and carboxymethylcellulose. Hence,the purpose of this experiment is to investigate the effect of three different additives on the production of bacterial cellulose by Acetobacter xylinum.Generally,there are three major parts in completing the research on production of bacterial cellulose by Acetobacter xylinum. The first part is preparation of inoculum by Acetobacter xylinum strain.The inoculum of Acetobacter xylinum is mother culture where later on will be used for the next fermentation process for the synthesis of bacterial cellulose.In the second part,the experiment was proceed for bacterial cellulose synthesis.Firstly,the inoculum of Acetobacter xylinum was prepared in the HS-medium. After obtaining the optimum yield of bacterial celullose production with different parameter of pH medium,three different additives were used at various concentrations to enhanced bacterial cellulose production.All the medium fermentation was incubated 30°C for 3 days.The optimum pH value was determined by the weight of bacterial cellulose, where the medium fermentations were incubated for three days.The production bacterial cellulose was relatively high with similar properties to that produced in HS medium.Wet weight of bacterial cellulose production by Acetobacter xylinum without microcrystalline cellulose was 0.1097g, while bacterial cellulose production was the highest, 0.589 g, at 0.2% MCC. Besides that, the results show that these samples consist of ultrafine fibrils,which form the reticulated structure.The additions of additives into the medium does not effect the structure of the cellulose.These results suggest that it is possible to produce bacterial cellulose from low-cost resources in order to increase its production to a larger scale.